Research Panorama on the Second Green Revolution in the World and Colombia - Alba, Ángela; Burgos, Ángela; Cárdenas, Jorge; Lara, Katherine; Sierra, Adriana; Montoya Rojas, Grace Andrea (TECCIENCIA, 2013)
The second Green Revolution is understood as the development of transgenic varieties, using tools such as genetic engineering and molecular biology applied to the DNA molecule. The product of the second Green Revolution corresponds to genetically modified organisms (GMOs) developed from inter-species cross manipulation and genetic information of some species of interest. The second Green Revolution was established as a strategy to help ensure food security, an increasingly growing population, and demanding of resources, to optimize crop productivity improving or introducing specific characteristics such as resistance to insects and herbicide tolerance to allow GMOs to be more tolerant of natural aggression. The debate on this revolution is maintained, sharpening and raising many interests due to its transversal aspects and impact on social, scientific, economic, political, and ecological issues. This paper aims to review the history, development, and applications of the second Green Revolution framed within the advantages and disadvantages of the environmental components that interact on the soil. Due to the impact of the techniques used by the second Green Revolution and the various complex interactions among different environmental components, this paper provides a panoramic description open to discussion and research in soil science and landscape ecology, leading the precise determination of the conditions generated in the natural and human environment. To conclude, a SWOT analysis is made available of transgenesis in environmental components.